Meeting global health challenges through operational research and management science - Geoff Royston
This paper considers how operational research and management science can improve the design of health systems and the delivery of health care, particularly in low-resource settings. It identifies some gaps in the way operational research is typically used in global health and proposes steps to bridge them. It then outlines some analytical tools of operational research and management science and illustrates how their use can inform some typical design and delivery challenges in global health. The paper concludes by considering factors that will increase and improve the contribution of operational research and management science to global health.